Effect of Relatively Low Levels of Porosity on the Plasticity of Metals and Implications for Profilometry‐Based Indentation Plastometry. Issue 12 (5th July 2022) - Reiff-Musgrove, Rebecca; Gu, Wenchen; Campbell, Jimmy E.; Reidy, John; Bose, Animesh; Chitrapur, Aadithya; Tang, Yuanbo; Burley, Max; Clyne, Trevor William
Abstract : Herein, the effect of dispersed (relatively low levels of) porosity within a metal on its plastic deformation is examined. Stainless steel samples, made via additive manufacturing, are used in the work. It's found that porosity reduces stress levels during yielding and work hardening, approximately in proportion to the pore content. There is no significant difference between the strength of the effect during tension and compression, although porosity does reduce the tensile ductility. Finally, the profilometry‐based indentation plastometry (PIP) methodology (for obtaining stress–strain curves from indentation testing) are used. Porosity tends to bring the inferred yield stress down more strongly than during tensile testing and give higher initial rates of work hardening. This is associated with high local strains near the indenter causing closure of pores, so that volume is not conserved during the test. The resultant reduction in the pile‐up around the indent creates errors in the inferred stress–strain curve. Abstract : Both uniaxial and profilometry‐based indentation plastometry (PIP) testing are applied to samples with and without dispersed porosity. In uniaxial loading, plastic deformation is little affected, with yield stress and work hardening rate reduced only in proportion to the pore content. PIP‐derived plots, however, incorporate somewhat lower yield stresses and higher work hardening rates for the porous samples.